URINARY AMMONIUM EXCRETION BY ALDOSTERONE THROUGH THE REGULATION OF RH C GLYCOPROTEIN IN THE INTERCALATED CELLS OF THE RENAL COLLECTING DUCT. (April 2021) - Izumi, Yuichiro; Eguchi, Koji; Ono, Makoto; Hiramatsu, Akiko; Inoue, Hideki; Nakayama, Yushi; Nonoguchi, Hiroshi; Kakizoe, Yutaka; Kuwabara, Takashige; Mukoyama, Masashi
Abstract : Objective: Aldosterone is a key hormone that regulates sodium reabsorption in the principal cells (PCs) of the renal collecting duct, maintaining blood pressure. Alternatively, aldosterone is involved in urinary acid excretion mainly via ammonia as ammonium ions in the intercalated cells (ICs) of the collecting duct, although its mechanisms are obscure. Rh C glycoprotein (Rhcg), an ammonia transporter, is expressed mainly in the intercalated cells. Direct regulation of ammonium excretion by aldosterone through the Rhcg in metabolic acidosis was investigated. Design and method: C57BL/6J mice were divided into four groups: 1) sham-operation, 2) sham and NH4Cl drinking (Sham-NH4Cl), 3) adrenalectomy and NH4Cl drinking (ADX-NH4Cl), and 4) adrenalectomy with continuous administration of aldosterone and NH4Cl drinking (ADX-Aldo-NH4Cl). Mice were sacrificed three days after NH4Cl drinking. Urinary ammonium excretion and localizations of Rhcg and ubiquitin were examined. For in vitro experiments, IN-IC cells, an intercalated cell-derived cell line, that stably express flag-tagged Rhcg (Rhcg-flag) were generated. The effects of aldosterone, spironolactone, Go6983 (a PKC inhibitor) and MG132 (a proteasome inhibitor) on the expression of Rhcg-flag were examined. Results: NH4Cl-induced urinary ammonium excretion was inhibited by adrenalectomy in ADX-NH4Cl mice. Aldosterone replacement restored ammonium excretion in ADX-Aldo-NH4Cl mice. Immunohistochemical study revealed that NH4Cl drinking increased the accumulation of Rhcg at apical and basolateral membranes and subapical sites of the ICs in sham-NH4Cl mice. Adrenalectomy and aldosterone replacement decreased and increased the accumulation of Rhcg at apical membrane of the ICs in ADX-NH4Cl and ADX-Aldo-NH4Cl mice, respectively. Ubiquitin expression was not changed between in PCs and ICs of sham-NH4Cl mice, while it was less in ICs than in PCs in ADX-NH4Cl mice. Aldosterone restored the ubiquitin expression in ICs. In IN-IC cells, Western blotting showed that aldosterone increased the expression of Rhcg-flag in the membrane fraction. Spironolactone and Go6983 each inhibited the expression of Rhcg-flag. Treatment with MG132 increased the expression of Rhcg-flag in whole cell lysate. Immunoprecipitation revealed the association of Rhcg with the ubiquitin. Conclusions: Aldosterone could directly regulate Rhcg expression through the mineralocorticoid receptor-PKC pathway. Furthermore, aldosterone could modulate Rhcg expression through the ubiquitin-proteasome pathway.